Investigation of Gynura segetum root extract (GSrE) induced hepatotoxicity based on metabolomic signatures and microbial community profiling in rats - Gu, Xinyi; Li, Shuwei; Lu, Mengna; Li, Ying; Wang, Qixue; Chen, Long; Jia, Yiqun; Cao, Shan; Zhang, Ting; Zhou, Mingmei; Gou, Xiaojun (Frontiers in Microbiology, 2022)
Recent years many reports focus on the hepatotoxicity of Gynura segetum root extract (GSrE), but the toxicological mechanism of GSrE is still unclear. This study is to investigate the mechanism of GSrE-induced hepatotoxicity of different doses and exposure durations by combining metabolomics and gut microbiota analysis. SD rats were divided into 3 groups: blank, low-dose (7.5 g/kg) and high-dose (15 g/kg) groups. Urine and feces samples were collected at the 0, 10, and 21 days. Metabolomics based on gas chromatography-mass spectrometry (GC-MS) was carried out to identify metabolites and metabolic pathways. 16S rDNA gene sequencing was applied to investigate the composition of gut microbiota before and after GSrE-induced hepatotoxicity. Finally, a correlation analysis of metabolites and gut microbiota was performed. Differential metabolites in urine and feces involved amino acids, carbohydrates, lipids, organic acids and short chain fatty acids. Among them, L-valine, L-proline, DL-arabinose, pentanoic acid, D-allose and D-glucose in urine and D-lactic acid and glycerol in fecal metabolites were the time- and dose-dependent differential metabolites. In addition, 16S rDNA sequencing analysis revealed that GSrE-induced hepatotoxicity significantly altered the composition of gut microbiota, including f_Muribaculaceae_Unclassified, Lactobacillus, Bacteroides, Lachnospiraceae_NK4A136_group, f_Ruminococcaceae_Unclassified, Prevotellaceae_Ga6A1_group and Escherichia-Shigella. The correlation analysis between gut microbiota and differential metabolites showed the crosstalk between the gut microbiota and metabolism in host involving energy, lipid and amino acids metabolism. In summary, our findings first revealed peripheral metabolism and gut microbiota disorders with time- and dose-dependent relationship, and the correlation between gut microbiota and metabolites in GSrE-induced hepatotoxicity.